Using my Demons to Make Good: The Short- and Long-Term Impact of Participating in Suicide-Related Research - Littlewood, Donna L.; Harris, Kamelia; Gooding, Patricia; Pratt, Daniel; Haddock, Gillian; Peters, Sarah (Archives of suicide research, 2021)
Participation in suicide-related research is generally associated with more positive than negative outcomes. However, sparse research has examined the longevity of any effects of participation. Here, we report the first qualitative examination of both the immediate and long-term views of participating in suicide-related research interviews. Thematic analysis indicated that participants had positive experiences, including increased altruism and self-understanding. For some participants, these benefits remained in the months post-participation. Follow-up data revealed that participants can be susceptible to short-term dips in mood, which may not emerge until a few hours/days post-participation. However, any negative effects of participation were confined to the days immediately following the study. Participant-informed recommendations were developed to support researchers in optimizing the well-being of participants in suicide-related research.